Microarray-Based Evaluation of Whole-Community Genome DNA Amplification Methods - Wang, Jian (American Society for Microbiology, 2011)

(untitled)
Three whole-community genome amplification methods, Bst, REPLI-g, and Templiphi, were evaluated using a microarray-based approach. The amplification biases of all methods were <3-fold. For pure-culture DNA, REPLI-g and Templiphi showed less bias than Bst. For community DNA, REPLI-g showed the least bias and highest number of genes, while Bst had the highest success rate and was suitable for low-quality DNA.